Evolving methodologies in the management of preserved removed parts in Japanese architectural cultural properties - Yohei Kiyonaga (Japan Architectural Review)
Abstract In this inquiry, the author intends to investigate the evolving methodologies in the management of preserved removed parts within the scope of Japanese architectural cultural properties, as recognized by the national government. Central to this examination is a focus on the selection criteria stipulated in the official preservation guidelines. This exploration involves a comprehensive analysis structured in three phases: firstly, scrutinizing the modifications in selection criteria as delineated in the guidelines governing repair projects; secondly, compiling and categorizing additional designated preserved removed parts recognized as cultural properties into six distinct types; and thirdly, identifying the inaugural instances of such preserved components or the initial reports pertaining to repair projects. Through this multifaceted research approach, the study endeavors to elucidate the evolving methodologies in the management of preserved removed parts in the realm of Japanese architectural cultural properties.